TINGKAT KONSUMSI DAN STATUS GIZI BALITA 12-36 BULAN DI WILAYAH KERJA PUSKESMAS NANIA - Lestaluhu, Santi Aprilian; Candriani, Candriani (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2023)
Background: Lack of consumption of macronutrients such as energy, protein and micronutrients such as iron, zinc, calcium and vitamin A, especially during the growth period, will disrupt a child's growth process, resulting in stunting. Objective: To determine the description of the consumption level of toddlers and the nutritional status of toddlers aged 12-36 years in the Nania Community Health Center working area. Method: This type of research is descriptive, namely: to determine the description of consumption levels for toddlers aged 12-36 months in the Nania Community Health Center Working Area. The population in this study were toddlers aged 12-36 years who lived in the Nania Health Center Working Area with a total of 671 toddlers. In this study, a sample of 67 toddlers was obtained through calculating the Solvin formula and then selected using a purposive sampling analysis technique. The research instrument used in this study was a questionnaire and a 24-hour food recall form and accompanied by TB/PB measurements, BB weighing. Results: Based on the research results, it is known that the number of toddlers aged 12-36 months in the Nania Health Center Working Area, the nutritional status of toddlers is based on the BB/U index, namely malnutrition status (41.5%), the nutritional status of toddlers is based on the TB/PB/U index, short as much as 1.5%, while nutritional status based on BB/TB or BB/PB is Malnutrition as much as 44.8%. From 57 samples, it was found that the energy consumption level of toddlers was mostly deficit, namely 56.7%, the protein consumption level of toddlers was a deficit of 16.4%, and the level of Vitamin A consumption deficit was 56.7%. While calcium, iron and vitamin C are also deficient, the value is 95.6%.